2022
DOI: 10.15388/omee.2022.13.83
|View full text |Cite
|
Sign up to set email alerts
|

The Role of Green Self-Identity and Self-Congruity in Sustainable Food Consumption Behaviour

Abstract: The aim of this paper is to explore the role of green self-identity and self-congruity with green food products in predicting consumers’ sustainable food consumption behaviour. Previous research suggests that there is a relationship between individuals’ self-identity and the consumption of products. However, when it comes to the realm of sustainable food consumption, those relations are not unambiguous. This study employs a survey with a sample of 837 respondents in Lithuania. The findings… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 49 publications
2
3
0
Order By: Relevance
“…Second, concerning intrinsic factors, the findings indicate that factors motivating Ecuadorian and Peruvian college millennials to consume organic products include health, habits, environmental awareness, and environmental knowledge. These findings are consistent with other researchers', who found that consumers purchase these products for health reasons [6,38,55,57], habits [6,56], awareness [19,[60][61][62], and knowledge [27,[63][64][65]. Additional research supports the other two intrinsic factors (attitudes and values), indicating that attitude is a significant predictor influencing organic purchasing behavior [7,17,36,42,46] and that consumer values increase the willingness to buy organic products [43,71,72].…”
Section: Discussionsupporting
confidence: 90%
See 3 more Smart Citations
“…Second, concerning intrinsic factors, the findings indicate that factors motivating Ecuadorian and Peruvian college millennials to consume organic products include health, habits, environmental awareness, and environmental knowledge. These findings are consistent with other researchers', who found that consumers purchase these products for health reasons [6,38,55,57], habits [6,56], awareness [19,[60][61][62], and knowledge [27,[63][64][65]. Additional research supports the other two intrinsic factors (attitudes and values), indicating that attitude is a significant predictor influencing organic purchasing behavior [7,17,36,42,46] and that consumer values increase the willingness to buy organic products [43,71,72].…”
Section: Discussionsupporting
confidence: 90%
“…Mentioned twenty-seven times by Ecuadorian and Peruvian millennials, it indicates that awareness of environmental issues among this cohort encourages consumption behaviors that favor environmental protection. This aligns with research suggesting that environmental knowledge is a key factor that enhances consumer awareness, enabling them to understand the impact of human activities on the environment due to unchecked consumption [27]. Furthermore, conscious consumption is often influenced by the extent of a consumer's knowledge about the environmental consequences of their consumption choices [7,[63][64][65].…”
Section: Environmental Knowledgesupporting
confidence: 70%
See 2 more Smart Citations
“…Meanwhile, the cognitive dimension is about the level of knowledge that a person has regarding the environmental degradation that occurs with each of the daily activities of human beings [42]. Several studies related to green consumption have incorporated GSI within their research models [29,43], which have determined that a common factor within this research is that an individual's self-perception can be an important determinant of green purchasing behaviors [45]. For example, Whitmarsh and O'Neill [46] identified that GSI is related to the intention to buy organic products.…”
Section: Green Self-identitymentioning
confidence: 99%